2002
DOI: 10.1515/cclm.2002.029
|View full text |Cite
|
Sign up to set email alerts
|

Intermethod Variation in Serum Carcinoembryonic Antigen (CEA) Measurement. Fresh Serum Pools and Control Materials Compared

Abstract: This study was undertaken to evaluate the feasibility of using commercial control materials in a regional external quality assessment scheme (EQAS) for serum carcinoembryonic antigen (CEA) measurement. We have assessed the commutability of 12 commercial control materials using five automated immunochemical systems. We compared the intermethod behavior of the materials with that of 12-14 patient serum pools. In a total of 48 comparisons (12 materials x 4 pairs of analytical systems), seven instances of non-comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…9, 2004 samples in the evaluated assays. Two recently published studies showed the perverse effect of recalibrating immunoassays measuring cardiac or tumor markers with noncommutable materials and the consequent misinterpretation of patient results (11,12 ). As demonstrated previously for another proposed CK-MB reference material (13 ), our results show that the AACC CK-MB standardization material cannot be used to directly calibrate commercial assays without rigorous verification of its commutability among procedures.…”
Section: To the Editorsupporting
confidence: 49%
“…9, 2004 samples in the evaluated assays. Two recently published studies showed the perverse effect of recalibrating immunoassays measuring cardiac or tumor markers with noncommutable materials and the consequent misinterpretation of patient results (11,12 ). As demonstrated previously for another proposed CK-MB reference material (13 ), our results show that the AACC CK-MB standardization material cannot be used to directly calibrate commercial assays without rigorous verification of its commutability among procedures.…”
Section: To the Editorsupporting
confidence: 49%
“…Investigations are needed to determine whether and how much influence the spiking has on the EQA results. Nevertheless, manufacturer-dependent differences could also be observed within patient samples by several other researchers [10,11,15,16], so our observed manufacturer-specific results are most likely not caused by the spiked material alone. Other EQA providers also used spiked sample materials [12,33] and especially Sturgeon et al deemed that a lack of commutability was unlikely due to the minimal manipulation of the sample material [19].…”
Section: Discussionmentioning
confidence: 55%
“…The glycoproteins AFP and CEA have long been approved as biomarkers, with International Reference Preparations (IRPs) having been available since 1975 [ 9 ]. Even though these reference standards have been around for decades, multiple studies have reported method- or manufacturer-dependent differences for both markers [ 10 , 11 , 12 , 13 , 14 , 15 ]. The Society for Promoting Quality Assurance in Medical Laboratories (INSTAND) is a German, non-profit interdisciplinary scientific medical society.…”
Section: Introductionmentioning
confidence: 99%
“…lyophilized samples) than with native patient samples. 5,6 Annals of Clinical Biochemistry 2010; 47: 171-173…”
Section: Introductionmentioning
confidence: 99%
“…lyophilized samples) than with native patient samples. 5,6…”
Section: Introductionmentioning
confidence: 99%